2022
DOI: 10.1001/jamanetworkopen.2022.26804
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Sex Disparities in Gout Prevalence Among US Adults

Abstract: IMPORTANCE Emerging data suggest gout and hyperuricemia may now be more frequent among Black adults in the US than White adults, especially Black women. However, national-level, sex-specific general population data on racial differences in gout prevalence and potential socioclinical risk factors are lacking. OBJECTIVE To identify sex-specific factors driving disparities between Black and White adults in contemporary gout prevalence in the US general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 78 publications
1
36
0
Order By: Relevance
“…We found that the Asian vs White disparity in gout prevalence and serum urate concentrations in the NHANES 2017 to 2018 and those in the UKBB through 2021 increased after accounting for social determinants of health, lifestyle, and clinical factors. This is in striking opposition to the gout disparity observed among Black individuals, which was entirely explained by the same socioclinical and lifestyle factors (ie, nurture), whereas Asian disparities are likely associated with both nature (genetics) and nurture (Westernized environments). Indeed, individuals of Asian ancestry have a higher prevalence of SLC2A9 , ABCG2 , and other urate risk variants, which are key contributors to hyperuricemia and gout .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…We found that the Asian vs White disparity in gout prevalence and serum urate concentrations in the NHANES 2017 to 2018 and those in the UKBB through 2021 increased after accounting for social determinants of health, lifestyle, and clinical factors. This is in striking opposition to the gout disparity observed among Black individuals, which was entirely explained by the same socioclinical and lifestyle factors (ie, nurture), whereas Asian disparities are likely associated with both nature (genetics) and nurture (Westernized environments). Indeed, individuals of Asian ancestry have a higher prevalence of SLC2A9 , ABCG2 , and other urate risk variants, which are key contributors to hyperuricemia and gout .…”
Section: Discussionmentioning
confidence: 72%
“…The excess burden of gout among Asian adults was replicated in the UK, another prototypical Western country (although with modestly better metabolic health than the US), and in both settings, these disparities strengthened after adjustment for BMI and socioclinical factors. This contrasts the Black vs White gout disparity in the US and likely reflects the combined effects of the higher prevalence of urate risk alleles and exposure to increasingly gout-prone environments among Asian individuals.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The key cause of primary HUA is a combination of low UA excretion and high UA production. A majority (67%) of UA in the human body is produced by the catabolism of nuclear proteins, nucleic acids, and other substances in the body; the remaining 33% comes from purines in food ( Lai et al., 2021 ; Lee et al., 2022 ; Mccormick et al., 2022 ). Adenosine deaminase (ADA) and xanthine oxidase (XO) are the key enzymes that regulate the production of UA during the catabolism of purine substances to UA.…”
Section: Introductionmentioning
confidence: 99%